Low birth weight and food insecurity at home in Pasto-Colombia - Morillo-Rosero, Héctor Hernán; Rojas-Botero, Maylen Liseth (Universidad y Salud, 2019)
Introduction: Birth weight is an important indicator of the health of the newborn and of the mother. It can also be used as a parameter to define sanitary conditions of societies. Low birth weight is well known as the main cause of morbidity and mortality in childhood. Objective: To determine the association between home food security during the last trimester of pregnancy and low birth weight. Materials and methods: A cases and controls study that included 73 full-term newborns with low weight and 73 normal weight neonates. Demographic, clinical and food security variables were analyzed. Results: Low birth weight was associated with home food insecurity (OR: 19,3; CI 95%: 6,5-56,9), when adjusted to mother’s arterial hypertension, vaginosis, antecedent of premature rupture of membranes and gestational malnutrition. Conclusions: We found a significant association between home food insecurity during the last gestational trimester and low birth weight of neonates born in San Pedro Hospital, Pasto. The strength of this association could be underestimated in the absence of adjustments to demographic and clinical variables.